Design and Evaluation of Multimedia-Based Interactive E-Teaching Materials for Enhancing Critical Thinking and Interest Learning in Elementary Mathematics: An ADDIE Approach - Mardiyanti, Diyah; Gunawan (Universitas Islam Negeri Raden Intan Lampung, 2026)
Elementary mathematics learning often remains dependent on printed materials and teacher-centered explanation, limiting students’ opportunities to engage with concepts visually, interactively, and critically. This study aimed to develop and evaluate multimedia-based interactive e-teaching materials designed to enhance fifth-grade students’ mathematical critical thinking skills and learning interest in the topic of circumference and area of plane figures. The study employed a research and development approach integrated with a quasi-experimental evaluation. The product was developed through the ADDIE model, covering analysis, design, development, implementation, and evaluation. Participants were fifth-grade students at UMP Elementary School, Banyumas Regency, Indonesia. Product validity was examined through media and material expert assessments, practicality was measured using teacher and student response questionnaires, and effectiveness was tested by comparing an experimental class using the developed e-teaching materials with a control class using conventional materials. The results showed that the product was valid, with media expert validation reaching 83.35% and material expert validation reaching 98.18%. Practicality was also very high, as indicated by the teacher response score of 97.78% and the student response average of 89.29%. The experimental class achieved higher critical thinking scores than the control class, 85.75 versus 67.75, and higher learning interest, 81.83 versus 72.00. The t-test results confirmed significant differences between the two groups, with p < .05. These findings demonstrate that multimedia-based interactive e-teaching materials can function as integrated cognitive and motivational scaffolds in elementary mathematics learning.